The art produced by substitute surfaces in hand block printing. (3rd June 2019) - Seidu, Raphael Kanyire
Abstract : Purpose: The purpose of this study is to identify the print effects produced on selected fabrics due to the adaptation of styrofoam, plastic net and wood as stamp blocks for printing. Design/methodology/approach: The art-based experimental research approach was used to produce and identify the art (prints) produced by stamp blocks on different fabrics using water-soluble print paste. Findings: They stamp block surfaces used in the block printing process produced interesting effects or prints that are uniquely associated with each other. Fabrics such as silver and satin produced shinny print effects coupled with a tough hand or feel as compared to a paperish hand produced on the surfaces of cotton-polyester blend and linen fabrics. The addition of white glue to the paste produced a smooth and embossed-like print effect on fabrics like mercerised cotton and linen. Further results were captured to indicate the hand of these fabrics after printing due to the change in viscosity of the print paste. Originality/value: The use of calabash and wood surfaces as stamp blocks used in Ghana and the rest of the world is common for printing patterns on fabrics. This study essentially reveals the possibility of using different surfaces for stamp blocks which produce aesthetically pleasing print effects. This when adopted by craftsmen and students would widen the teaching and creative scope in block printing and further produce viable prints for the market using available materials in the environment. These activities would promote and maintain the philosophy of block printing even in the era of advance printing technologies.